APA Referencing: A Handbook. - Library, MIE; Conneally, Clare; Patton, Trish (Marino Institute of Education Library, 2022)
This handbook covers why, how, and when to reference, in the APA7 format. When you are writing an essay or report, you will support your answer or back up your argument by discussing published work. These published works could be books, textbooks, articles, online sources, videos, newspaper articles, among others. Referencing is the system by which you keep track of and give credit to the sources you have mentioned in your essay. Referencing is a requirement in academic writing, and you will be asked to present a list of all the works and authors cited in your essay.
Keywords: APA; Handbook; APA7 Referencing; Referencing; Library Support; Academic Skills; Academic Integrity; APA7; Educational Resource; Writing Skills; Education--Ireland